Evaluation of physiological traits of summer maize under drought stress. (17th February 2016) - Yan, Weiming; Zhong, Yangquanwei; Shangguan, Zhouping
ABSTRACT: A study was conducted to investigate the sensitivity of physiological traits under different soil water availability in summer maize ( Zea mays L.). Plant growth (plant height and stem), water relations (relative water content), gas exchange (net photosynthesis rate, stomatal conductance and transpiration rate) and nutrient levels were measured after 5, 10, 15 and 20 days of drought with different soil water availability. We found that all these physiological traits were inhibited by drought stress, but they showed differing levels of sensitivity with different soil water availability. Our results show that stomatal conductance was the most sensitive in mild drought conditions, that carbon accumulation was more sensitive than the other parameters in moderate drought, and that height and stem showed the largest response ratio in severe drought conditions. Different traits performed differently under drought conditions; thus, choosing an adequate index for evaluating soil water availability is necessary for maize cultivation.